Social Capital For Rural Community During the Covid-19 Pandemic in Banyumas Regency - Pandu Primadata, Ankarlina; Yamin, Muhammad; Wardhianna, Sotyania; Sutoyo, Ign. Suksmadi; Kurniawan, Agung; Citra Permata, Fadhila (KnE Social Sciences, 2023)
The COVID-19 pandemic has significantly impacted Indonesian society. In addition to having an effect on the community’s socioeconomic aspects, it also has an effect on the health aspect. The most important factor in preventing and managing the effects of COVID-19 is how to foster social cohesion and make use of all community resources, especially its social capital. Finding out the social capital of rural communities amid the current COVID-19 outbreak is therefore urgently needed. This study’s specific goal is to examine the social capital that exists in rural Banyumas Regency villages during the COVID-19 pandemic and how such social capital influences local activities and rural populations’ social relations. A case study technique and a descriptive qualitative methodology were used to perform this study. The researcher will conduct in-depth interviews and direct observations to gather data. The Banyumas Regency’s rural settlements will be chosen for the study depending on the researcher’s criteria (purposive sampling). The findings demonstrated that several Banyumas Regency village areas had powerful social capital through social networks and community trust. Still, different things also occurred in several other regions, where the level of trust between community members had decreased since the pandemic. The social network that should exist in the community disintegrates or fails to form due to the drop in confidence. Keywords: Social Capital, Village Community, COVID-19 Pandemic